CONTEMPORARY ACTUALITIES AND CHALLENGES OF ASSESSMENT OF DEPRESSION IN ADOLESCENTS - Elsiņa, Inese (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Depression is one of the most widespread mental disorders worldwide. Adolescence is a vulnerable period for developing depression. It is associated with a number of challenges in biological, psychological and social areas. Depression, if left unassessed and untreated properly, has a great negative impact on well–being, mental and physical health, social functioning, academical achievement, and economical disadvantages on the national level as well. Studies reveal the need of improving the identification of depression symptoms in adolescents among different types of specialists working with them (i.e. in educational, primary care, clinical settings). Also, efficient measurement instruments and tools are evaluated to help specialists in assessment of the symptoms of adolescents’ depression more precisely. The aim of the current article is, firstly, to justify the actuality of the problem and the assessment of adolescents’ depression, secondly, to provide a theoretical review, integrative analysis of contemporary approaches to assessment of adolescents’ depression globally and in Latvia, thirdly, to describe the proximal research ideas and tasks of the author of this article on the topic.